MUSICAL WORK AS A SUBJECT OF AESTHETIC ANALYSIS IN THE WORKS OF R. INGARDEN (Pedagogy of Higher and Secondary Education, 2022)
In this article the analysis of musical work its peculiarities of performance and perception in R. Ingard’s monography (polish philosopher) is considered.
Keywords: 1